Ethoxy-ester functionalized imidazolium based ionic liquids for lithium ion batteries - Nirmale, Trupti; Khupse, Nageshwar; Gore, Rohitkumar; Ambekar, Jalindar; Kulkarni, Milind; Varma, Anjanikumar; Kale, Bharat (ChemistrySelect, 2018)
Ethoxy ester functionalized imidazolium and bis(tri fluoromethanesulfonyl)imide based ionic liquids (ILs) are synthesized and considered as electrolyte for lithium ion batteries. The series of ethoxy ester functionalized ionic liquids were chosen with increase in ethoxy unit from one to three, followed by polymeric units. These ionic liquids provide both ester and ethoxy groups as interaction sites for Li+ ions enhancing the Li+ ion transportation, resulting in ionic conductivity of 10(-3) Scm(-1) at 25 degrees C, which is of 10(3) factor higher than ethoxy containing polyethylene oxide solid polymer electrolyte. It's noteworthy that the conductivity increases as ethoxy units are increased from one to three units, followed by a decrease for the polymeric ethoxy unit. Electrochemical stability window of these ionic liquids improves as the ethoxy groups are added to imidazolium cation. The Li/LiFePO4 cell fabricated with [ME(3)AMIm][TFSI] electrolyte shows good initial discharge capacity of 98.5 mAhg(-1) at 0.05 C-rate at room temperature, which gradually decreases with cycling. Systematic investigation of electrode surfaces by using SEM and EDX shows deposition of passivation layers on their surfaces. Ionic liquids fabricated by this facile method provide a promising model system for understanding the molecular interactions in promoting the lithium-ion conduction mechanism. The advantages and the limits associated to series of ionic liquid electrolytes are critically investigated.